Methods of the determination to number of the active population of the region state and forms their action in condition of the intensification social-political situation - Orlov М. М. (Honor and Law, 2019)
Modern social-political situation in state requires the deep analysis of the possibilities of arctic power and determinations of their factors. Methods of the determination to number of the active population of the region state and forms their action in condition of the intensification social-political situation are considered.